Anti-fouling Behavior of Polyethersulfone-Coated Glass Fibre Reinforced Polymer Composite - Abdul Kadir, Muhammad Hazim; Hashim, Mohd Akmal; Hashim, Ummu Raihanah; Jumahat, Aidah (International Journal of Sustainable Construction Engineering and Technology, 2024)
In the realm of marine construction and structural applications, coatings are essential in preventing the accumulation of fouling organisms, acting as a barrier against unwanted particles, contaminants, and microorganisms. However, traditional coating materials face limitations in resisting fouling growth, often accompanied by various drawbacks. This study delves into the fouling growth behaviour or mechanisms and its anti-fouling properties of glass fibre reinforced polymer (GFRP) composites that is coated with polyethersulfone (PES) in real marine environment. In this study, a commercial coating material, namely Kossan paint coating, was used as reference and the fouling growth mechanisms on various types of surfaces were compared to this reference material. The primary aim is to assess the performance of these coatings over time, i.e., 0, 14, 28, 60, 90, and 120 days, in marine settings. The degree of biofouling attachment on the samples was evaluated through visual observation and image J analysis. Results showed that glass fibres coated with Kossan paint exhibited a lower percentage of bio-fouling attachment compared to those with PES coatings. However, despite its efficacy in reducing biofouling, Kossan paint tends to detach from the glass fibre surface, necessitating repainting every four months, leading to higher maintenance costs. In contrast, PES coatings demonstrated superior adherence to the glass fibre surface, suggesting their potential as effective anti-fouling coating material. Nonetheless, modifications in properties such as surface roughness, hydrophobicity, and wettability are needed for PES coatings to efficiently prevent bio-fouling growth. This study highlights the need for balancing fouling resistance and durability in coating materials for sustainable marine applications.